(untitled) (Proceedings of the International Conference on Social Sciences, 2018)
Experience of positive affect may help individuals to enhance psychological growth and well-being. This study examined the effect of positive affect on purpose in life and life satisfaction. Also, we intended to examine the moderating effect of gender on the link between positive affect and purpose in life and the link between positive affect and life satisfaction. The sample consisted of 200 participants (76 females and 124 males) and they responded to a questionnaire assessing positive affect, purpose in life and life satisfaction. Positive affect significantly predicted purpose in life and life satisfaction. There was a significant gender difference in purpose in life, that is, women rated higher on purpose in life than men. Further, the interaction between positive affect and gender was significant, indicating that the effect of positive affect on life satisfaction was moderated by gender.